Neuromyelitis optica: an overview. Issue 1013 (17th March 2010) - Nandhagopal, R; Al-Asmi, Abdullah; Gujjar, Arunodaya R
Abstract : Neuromyelitis optica (NMO) is a relapsing inflammatory disorder of the central nervous system that closely resembles multiple sclerosis. This review discusses recent understanding of NMO with reference to epidemiology, clinical spectrum, immunopathology, diagnostic evaluation, clinical course and management. Within the clinical spectrum of NMO, the classical form (with relapsing opticomyelitis) and limited forms (either recurrent myelitis or optic neuritis), as well as its association with other autoimmune disorders, have been recognised in recent years. Further, symptomatic or asymptomatic cerebral lesions may be present, and such brain lesions do not necessarily exclude the diagnosis. In the appropriate clinical context, the diagnosis is supported by longitudinally extensive myelitis on spinal MRI. Overwhelming evidence strongly indicates that aquaporin 4 antibody has a pathogenetic role in the development of NMO and serves as a useful diagnostic and prognostic marker. Detection of this autoantibody has led to the categorisation of NMO as an autoimmune channelopathy. NMO can be distinguished from multiple sclerosis by a combination of clinical, radiological and laboratory studies. However, the nosological position of Asian opticospinal multiple sclerosis is not settled. In NMO, acute attacks usually result in moderate to severe functional impairment, and, in the absence of a secondary progressive course (unlike relapsing–remitting multiple sclerosis), prevention of relapses is of crucial importance in the management of the disease. Indeed, relapse prevention with long-term immunosuppressive medication remains the cornerstone of therapy in this otherwise debilitating disease!